Multiple Motivations to Read Young Adult Literature in the Lives of Three African-American Middle School Males - Susan Groenke; Stacey Reece; Allison Varnes (Study and Scrutiny)
In this article, we share what young adult literature three male African-American adolescent participants in this study—Tariq, Tyrell, and Tyrone—chose to read when given opportunities to choose. We also share what they had to say about the literature, about reading, and about themselves as readers. The participants’ own words and text choices reveal much about what kind of young adult literature they find relevant, and why, and point to multiple motivations—both intrinsic and extrinsic, personal and social—for reading young adult literature.